2017
DOI: 10.1038/bjc.2017.227
|View full text |Cite
|
Sign up to set email alerts
|

Pre-diagnostic statin use, lymph node status and mortality in women with stages I–III breast cancer

Abstract: Background:Recent meta-analyses suggest that pre-diagnostic statin use is associated with reduced breast cancer-specific mortality. Studies have shown that high breast tumour expression of the statin target (3-hydroxy-3-methylglutaryl coenzyme-A reductase) is associated with lymph-node negative cancer. Therefore, we examined the association between pre-diagnostic statin use and; lymph node status, breast cancer-specific and all-cause mortality.Methods:Women with stages I–III breast cancer were identified from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 45 publications
4
21
0
Order By: Relevance
“…In fact, for 13 types of cancers, it was observed a decrease in cancer-related death risk in statin users [ 61 ]. The anti-tumoral effects of statins has also been described in variety of other cancer origins, for example, endometrial cancer (HR = 0.83; 95% CI = 0.69–1.01) [ 58 ], breast cancer (HR = 0.81; 95% CI = 0.68–0.96) [ 64 ], colorectal cancer (fully adjusted HR = 0.71; 95% CI = 0.61–0.84) [ 65 ] and prostate cancer (HR = 0.76; 95% CI = 0.66–0.88) [ 66 ]. These studies show the effect of statins to prevent the onset of cancer.…”
Section: Drug Repurposing For Ovarian Cancer Therapymentioning
confidence: 99%
“…In fact, for 13 types of cancers, it was observed a decrease in cancer-related death risk in statin users [ 61 ]. The anti-tumoral effects of statins has also been described in variety of other cancer origins, for example, endometrial cancer (HR = 0.83; 95% CI = 0.69–1.01) [ 58 ], breast cancer (HR = 0.81; 95% CI = 0.68–0.96) [ 64 ], colorectal cancer (fully adjusted HR = 0.71; 95% CI = 0.61–0.84) [ 65 ] and prostate cancer (HR = 0.76; 95% CI = 0.66–0.88) [ 66 ]. These studies show the effect of statins to prevent the onset of cancer.…”
Section: Drug Repurposing For Ovarian Cancer Therapymentioning
confidence: 99%
“…The characteristics of the included cohorts were shown in Table 1 . Eight of them were prospective cohort studies ( 12 , 14 , 16 18 , 25 , 26 , 28 ), while the other nine were retrospective ( 13 , 15 , 19 23 , 25 , 27 ). Women with breast cancer of different clinical stages were included.…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analysis of nine cohort studies ( 14 17 , 19 , 21 , 22 , 25 , 28 ) showed that statin use was associated with a significantly reduced risk of breast cancer mortality (adjusted HR = 0.80, 95% CI: 0.72 to 0.90; p < 0.001) with significant heterogeneity ( I 2 = 55%; Figure 4A ). Sensitivity analysis by omitting one study at a time showed similar results (HR: 0.79–0.86, p all <0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results caused researchers to pay attention to the antitumor effects of statins. After this study, antitumor effects were reported in similar epidemiological studies and basic research for other types of cancer, including colorectal cancer (fully adjusted HR=0.71; 95% CI=0.61–0.84) [23], prostate cancer (HR=0.76; 95% CI=0.66–0.88) [24], breast cancer (HR=0.81; 95% CI=0.68–0.96) [25], and endometrial cancer (HR=0.83; 95% CI=0.69–1.01) [26].…”
Section: Drugs Anticipated To Undergo Repositioning In Futurementioning
confidence: 92%